Controlled Release of Photoresponsive Nematic Liquid Crystalline Microcapsules. Issue 3 (27th January 2021) - Iwai, Yosuke; Maeda, Takatoshi; Uchida, Yoshiaki; Araoka, Fumito; Nishiyama, Norikazu
Abstract : Water‐in‐oil‐in‐water double emulsion with a photo‐responsive nematic liquid crystalline shell showing ultraviolet (UV) light‐triggered release of contents is successfully produced. Under UV light, the defects of the molecular orientational order caused by being sandwiched between the spherical interfaces gather together, the shell deforms, and the inner water droplets are released to the outer phase. Abstract : A water‐in‐oil‐in‐water double emulsion with a photoresponsive nematic liquid crystalline shell shows an ultraviolet (UV) light‐triggered release of contents. In the release process, the defects of the molecular orientational order, which are topologically essential for the shell sandwiched between the spherical interfaces, gather together, the shell deforms, and the inner water droplets are released to the outer phase.